Personal physical education of a teacher as a basis for building a positive attitude to physical education of students. - Bozsik N.V (Kharkov National Pedagogical University, 2011)
It is examined the nature and value of personal physical training for future subject teachers. It is shown that the physical education teacher - a powerful tool not only for physical improvement and rehabilitation, but also education and social, employment and creative activity of citizens. It is only when the prevailing culture of personal physical educator may carry out work in physical education. It is established that the personal physical culture is characterized by quality level of physical development and physical education aimed at self-development and improve their own health and the health of students. Finally, the concepts of "culture", "physical culture of personality."